2019
DOI: 10.21315/eimj2019.11.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Level and Sources of Stress Among Allied Health Sciences Students of Bayero University Kano: A Comparison Between Clinical and Pre-Clinical Students

Abstract: This study is to assess the level and sources of stress among allied health sciences students of Bayero University Kano. A total of 230 participants were recruited in this cross-sectional survey using stratified sampling technique. The data on level and sources of stress was assessed using medical student stressor questionnaire. Descriptive statistics of means, standard deviations, frequency and percentage were used to summarise the data while inferential statistic of independent t-test and oneway ANOVA were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Mehta et al 26 also reported that the major stressors faced by medical students were academic and group activity related. Additionally, the findings of Habeeb, 17 Othman et al, 27 Shelke et al, 28 Othman et al, 29 and Muhammad et al 30 indicated that ARS was the greatest stressor among the students. One plausible explanation for our results might be the fact that the medical and allied health science disciplines in the study setting are competitive learning environments, which only accept students with the highest grades.…”
Section: Discussionmentioning
confidence: 94%
“…Mehta et al 26 also reported that the major stressors faced by medical students were academic and group activity related. Additionally, the findings of Habeeb, 17 Othman et al, 27 Shelke et al, 28 Othman et al, 29 and Muhammad et al 30 indicated that ARS was the greatest stressor among the students. One plausible explanation for our results might be the fact that the medical and allied health science disciplines in the study setting are competitive learning environments, which only accept students with the highest grades.…”
Section: Discussionmentioning
confidence: 94%
“…Participants of this study reported strained relationships with the perpetrators, reduced self-confidence, decreased clinical output, depression and regretted career choice, while only a few resort to smoking and alcohol. These factors have been shown to contribute to the psychological stress experienced by these individuals, who are already strained mentally and physically by the taxing nature of the one mandatory clinical internship [14,21,22]. Suicidal ideation is having the thought of intentionally causing one's own death [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Students described examinations and a high workload as the major factors contributing to academic stress [10][11][12] . Interpersonal or social stressors with family and peers were cited in 15 studies 7,11,[13][14][15][16][17][18][19][20][21][22][23][24][25] . In another study conducted in Saudi Arabia, nursing students identified relationships with hospital staff to be a source of stress 26 .…”
Section: Sources Of Stressmentioning
confidence: 99%
“…Stress from clinical training was emphasised by 13 out of the 33 studies 7,13,17,18,20,[25][26][27][28][29][30][31][32] . Poorly staffed clinical departments, fast-paced wards and initial clinical placements were all factors contributing towards the stress of students 28 .…”
Section: Sources Of Stressmentioning
confidence: 99%
See 1 more Smart Citation